Experimental, Numerical, and Theoretical Studies of Bond Behavior of Reinforced Fly Ash-Based Geopolymer Concrete - Tuan Anh Le; Thuy Ninh Nguyen; Khoa Tan Nguyen (Applied Sciences, 2022)
This paper presents the results of an experiment study and suggests a theoretical formulation for the bond behavior of reinforced fly ash-based geopolymer concrete. Three grades (20 MPa, 30 MPa and 40 MPa) of a geopolymer concrete along with three reinforcement diameters (12, 16, and 20 mm) were selected for experimental work. The bond behavior of the reinforced geopolymer concrete is determined using pullout test, finite element analysis (FEA), and theoretical work. The test data indicated that the bond strength of reinforced fly ash-based geopolymer concrete increases about 1.97 to 2.56 times with the increase of compressive strength from 20.33 MPa to 41.12 MPa. For grade 30 MPa and 40 MPa specimens, the concrete cover to diameter ratio (c/db) increased up to 4.19 resulted in the increase of bond strength. Then, the bond strength decreases with the increase of the c/db ratio from 4.19 to 5.75, while grade 20 MPa specimens is vice versa. The bond-slip relations between the reinforcement and geopolymer concrete determined from FEA is in good agreement with experimental results. The coefficient of variation (CoV) is only 0.01. However, this behavior is quite different from the data calculated by the fib model.